Quality Work of Life, Job Satisfaction dan Social Support terhadap Employee Engagement Dosen Perguruan Tinggi Swasta di Surakarta - Nenden Nur Annisa; Diana Pramudya Wardhani; Fitria Amallia (Benefit: Jurnal Manajemen dan Bisnis, 2022)
The government evaluates the feasibility of higher education institutions in the implementation of education to see the quality of education in Indonesia through the accreditation of higher education institutions and their education programs. Accreditation of higher education institutions, especially private universities in Surakarta, is a necessity and an important thing in maintaining the quality of higher education. This study aims to determine the relationship between quality work of life, job satisfaction and social support on employee engagement of private university lecturers in Surakarta. This study uses quantitative methods and descriptive analysis. Sampling in this study is probability sampling with the type of simple random sampling, the number of respondents is 50 lecturers of private universities in Surakarta. The data analysis method used in this study is multiple linear regression analysis with data processing performed with the SPSS 22 for Windows program. The results of this study indicate that the quality of work of life has an effect on employee engagement, job satisfaction has no effect on employee engagement, and social support has an influence on employee engagement.Keywords: quality work of life, job satisfaction, social support, dan employee engagement